DESIGN AND ANALYSIS OF PHYSICAL MODELLING OF BAMBOO PILE WITH GREEN MUSSELS CULTIVATION COMBINATION BREAKWATER (BEADS MODEL) - Putri Pitaloka Sunarnjoto, Diah
Indonesia is world’s largest archipelagic country comprising over 17.000 islands, surrounded by waters. Indonesia has 95.181 km coastline, which is the second longest coastline in the world. This made abrasion inevitable in Indonesia’s coastal areas. Propagating waves approaching the shore causes coastal erosion resulting a coastline retreat. Therefore, natural coastal protection such as mangrove forests is needed to protect the coasts. To be able to reduce wave energy and height, mangrove trees need to have a strong root systems. To successfully grow and safe from incoming waves, a temporary breakwater structure made from bamboo poles is required. In Indonesia, green mussels culture using bamboo stakes are common. The usage of bamboo as a collector is the most effective, producing almost 10 kilograms of green mussels for one bamboo. Green mussels cultivation is best done in a mangrove ecosystem, so bamboo pile with green mussels cultivatin combination breakwater is very likely to be implemented in coastal areas in Indonesia. This study aims to observe the effectiveness of wave height reduction using various configurations of natural coastal protection, bamboo pile with green mussels cultivatin combination breakwater and variations in the distance between mangrove and bamboo pile through physical modelling. The laboratory experiments were conducted in a narrow 2D wave flume with ten waves representing Indonesia’s wave characteristics. This final project focuses on determiing the most effective configuration of combination breakwater by comparing the structure‘s and system‘s transmission coefficient (Kt). The experiment result shows that the average system of mangroves and bamboo pile with green mussels cultivatin combination breakwater effectively reduce 26.823% of the wave height. Based on the model experiment, the most effective configuration is the one with a total of 184 pile, distance between coloumns and rows are 100mm, distance between mangrove and breakwater is 700mm, and is 1500mm width. This configuration able to reduce 20% of wave height structurally, and 32.94% systemically.